Lieux communs et esthétique des fictions historiques numériques - Marc Marti (Cahiers de Narratologie)
We propose a twofold question applied to contemporary digital fiction: how do they recall the past and why do they recall it? The aim is not only to put cultural representations of history into historical perspective, but also to raise the question of the aesthetic construction of fiction and its development, from novels to video games and cinema. The historical nature of fictional creation will lead us to propose an aesthetic that takes this factor into account, using the example of video games.